Fabrication of capacitive gas sensor applying MoS2 nanoparticles by printing technique - Takumi MASUDA; Yuto KASUGA; Takahiro KONO; Arata KANEKO (Nihon Kikai Gakkai ronbunshu, 2023)
A capacitive MEMS gas sensor is fabricated by transfer printing of Au thin film and inkjet printing of molybdenum disulfide (MoS2) nanoparticles. The transferred Au thin film is formed to be a comb electrode with a width of 100 μm and a thickness of 50 nm, and the comb-like Au electrode surface becomes hydrophilic by UV irradiation. The MoS2 particles are deposited on the comb-like Au electrode as a sensing element, where the applied voltage and the pulse width of the piezoelectric inkjet head are adjusted to make a drop velocity of 6 m/s. The UV irradiation helps the MoS2 particles to be deposited uniformly while suppressing undesired aggregation of the particles. The fabricated sensor composed of the comb-like Au electrode and the film of MoS2 particles is placed in a chamber for testing, and the capacitance is measured with exposure to ethanol gas. It is demonstrated that the capacitance increases with exposure to ethanol gas and subsequently decreases after air-exposure. It is reasonable that the capacitance change is due to the adhesion of ethanol gas molecules to the MoS2 particle film, and that the fabricated structure works as a capacitive MEMS gas sensor. It is also found that there are variations in response due to the surface morphologies of the MoS2 particle film.